Assessing the impact of CHARM2, a family planning program on gender attitudes, intimate partner violence, reproductive coercion, and marital quality in India. - Sangeeta Chatterji; Nicole E Johns; Mohan Ghule; Shahina Begum; Sarah Averbach; Madhusudana Battala; Anita Raj (Public Library of Science (PLoS), 2024)
Using a two-armed cluster randomised controlled trial, CHARM2 (Counselling Husbands to Achieve Reproductive health and Marital equity), a 5-session gender equity and family planning intervention for couples in rural India, showed an impact on family planning outcomes in primary trial analyses. This study examines its effects on gender-equitable attitudes, intimate partner violence, reproductive coercion, and marital quality. We used multilevel mixed-effects models to assess the intervention impact on each outcome. Both male (aIRR at 9 months: 0.64, C.I.: 0.45,0.90; aIRR at 18 months: 0.25, C.I.: 0.18,0.39) and female (aIRR at 9 months: 0.57, C.I.: 0.46,0.71; aIRR at 18 months: 0.38, C.I.: 0.23,0.61) intervention participants were less likely than corresponding control participants to endorse attitudes accepting physical IPV at 9- and 18-month follow-ups. Men in the intervention, compared to those in the control condition, reported more gender-equitable attitudes at 9- and 18 months (ß at 9 months: 0.13, C.I.: 0.06,0.20; ß at 18 months: 0.26, C.I.: 0.19,0.34) and higher marital quality at the 18-month follow-up (ß: 0.03, C.I.: 0.01,0.05). However, we found no effects on women's experiences of IPV, reproductive coercion, or marital quality. CHARM2 shows promise in improving men's and women's attitudes towards gender equality and male perceptions of marital quality. Still, IPV and reproductive coercion reductions may require more intensive programming than that provided within this 5-session model focused on family planning.